Description of Loricyphes froehlichi, a new genus and species of Leptohyphidae (Ephemeroptera) from São Paulo, Brazil - Molineri, Carlos (2015)
Loricyphes froehlichi gen. et sp. nov. is described and illustrated from nymphs, subimago and eggs. Diagnostic characters include, in the nymph: head, thorax and abdomen with very large and pointed tubercles; maxillary palp absent; femora very long and slender, ratio length/maximum width=5; forefemur without transverse row of setae at dorsum and with few chalazae; tarsal claws with 12–17 marginal denticles, submarginal denticles absent; abdominal segments II–VII very wide and laterally expanded forming a shallow cavity for the dorsal-positioned gills; and in the egg: conic in shape, with one pole truncated and the other acute, polar capsule apparently absent, chorionic plates longitudinally arranged between longitudinal elevated ridges, adhesive filaments absent. The new genus is superficially similar to Coryphorus (Coryphoridae) but presents synapomorphies of Leptohyphidae, and it is probably related to Tricorythodes based on gill morphology.